Impact of Attention Biases to Threat and Effortful Control on Individual Variations in Negative Affect and Social Withdrawal in Very Young Children - Cole, Claire E. (J Exp Child Psychol, 2015)
Early temperamental sensitivity may form the basis for the later development of socioemotional maladjustment. In particular, temperamental negative affect places children at risk for the development of anxiety. However, not all children who show negative affect go on to develop anxiety or extreme social withdrawal. Recent research indicates that reactive control, in the form of attention to threat, may serve as a bridge between early temperament and the development of later social difficulties. In addition, variation in effortful control may also modulate this trajectory. Children (Mean(Age)=5.57 years) were assessed for attention bias to threatening and pleasant faces using a dot-probe paradigm. Attention bias to threatening (but not happy) faces moderated the direct positive relation between negative affect and social withdrawal. Children with threat biases showed a significant link between negative affect and social withdrawal, while children who avoided threat did not. In contrast, effortful control did not moderate the relation between negative affect and social withdrawal. Rather, there was a direct negative relation between effortful control and social withdrawal. The findings from this short report indicate that the relation amongst temperament, attention bias, and social withdrawal appears early in life and point to early emerging specificity in reactive and regulatory functioning.